Finding the Enemy Within : Blasphemy Accusations and Subsequent Violence in Pakistan - Ashraf, Sana (Canberra ANU Press, 2021)
In the past decade, Pakistan has witnessed incidents such as the public lynching of a student on a university campus, a Christian couple being torched alive, attacks on entire neighbourhoods by angry mobs and the assassination of a provincial governor by his own security guard over allegations of blasphemy. Finding the Enemy Within unpacks the meanings and motivations behind accusations of blasphemy and subsequent violence in Pakistan. This is the first ethnographic study of its kind analysing the perspectives of a range of different actors including accusers, religious scholars and lawyers involved in blasphemy-related incidents in Pakistan. Bringing together anthropological perspectives on religion, violence and law, this book reworks prevalent analytical dichotomies of reason/emotion, culture/religion, traditional/Western, state/nonstate and legal/extralegal to extend our understanding of the upsurge of blasphemy-related violence in Pakistan. Through the case study of blasphemy accusations in Pakistan, this book addresses broader questions of difference, individual and collective identities, social and symbolic boundaries, and conflict and violence in modern nation-states.
English
Keywords: Religious fundamentalism; Blasphemy, heresy, apostasy; Religious intolerance, persecution & conflict; Christianity; Christian spirituality & religious experience; Islam; Religious life & practice; Violence in society; Social & cultural anthropology, ethnography; Pakistan; blasphemy; Islam; violence; religion